On finitely equivalent continua - Janusz J. Charatonik (International Journal of Mathematics and Mathematical Sciences)
For positive integers m and n, relations between (hereditary) m- and n-equivalence are studied, mostly for arc-like continua. Several structural and mapping problems concerning (hereditarily) finitely equivalent continua are formulated.